Protein kinase A type I and type II define distinct intracellular signaling compartments. - Di Benedetto, G; Zoccarato, A; Lissandron, V; Terrin, A; Li, X; Houslay, MD; Baillie, G; Zaccolo, M (2008)
Protein kinase A (PKA) is a key regulatory enzyme that, on activation by cAMP, modulates a wide variety of cellular functions. PKA isoforms type I and type II possess different structural features and biochemical characteristics, resulting in nonredundant function. However, how different PKA isoforms expressed in the same cell manage to perform distinct functions on activation by the same soluble intracellular messenger, cAMP, remains to be established. Here, we provide a mechanism for the different function of PKA isoforms subsets in cardiac myocytes and demonstrate that PKA-RI and PKA-RII, by binding to AKAPs (A kinase anchoring proteins), are tethered to different subcellular locales, thus defining distinct intracellular signaling compartments. Within such compartments, PKA-RI and PKA-RII respond to distinct, spatially restricted cAMP signals generated in response to specific G protein-coupled receptor agonists and regulated by unique subsets of the cAMP degrading phosphodiesterases. The selective activation of individual PKA isoforms thus leads to phosphorylation of unique subsets of downstream targets.